Housing and sanitation-related diseases - Fabio Nobuo Nishimura (Economia Aplicada, 2020)
Housing and health-related issues are typical concerns of developing countries since their consequences usually lead to deadly diseases. Hence, in order to improve the assertiveness of public policies, minimize the divergence between actions proposed by different studies and contribute to mitigate those issues, this paper seeks to understand the relative impacts of the proposed policies as well as their efficiency. Thus, this paper evaluates the Brazilian Rental Housing Program (RHP) using a regression discontinuity design (RDD) model, a strategy that is strengthened by the performance of robustness tests. As a result, we verified that RHP was able to reduce deaths from sanitation-related diseases by up to 11% and that this effect increases over time.